Enhancing Linguistic Intelligence: The Effects of the Show and Tell Method on 5-6 Year-Olds - Ibria Julita, Dedek; Puspa Juwita, Rani (Journal of Islamic Education Students (JIES), 2024)
This study aims to determine the effect of the Show and Tell method on linguistic intelligence among children at RA Al-Ikhsan, Banda Aceh. This quantitative research utilizes a pre-experimental design with a one-group pre-test post-test design. The sample consists of all 15 students from Class B, selected using a total sampling technique. Data were collected using an observation sheet as the research instrument and analyzed through normality tests and hypothesis testing. The research findings indicate that the average pre-test score was 45.56%, while the average post-test score was 76.11%. The normality test resulted in a value of 0.524, and the t-test analysis yielded a significance value of <0.000, which is less than α = 0.05. Based on this data, it can be concluded that the alternative hypothesis (Ha) is rejected, and the null hypothesis (Ho) is accepted. Therefore, the study concludes that the Show and Tell method using the butterfly cycle media has a significant impact on linguistic intelligence among children at RA Al-Ikhsan, Banda Aceh.